Do drinking-age laws have an impact on crime? Evidence from Canada, 2009–2013. (1st October 2016) - Callaghan, Russell C.; Gatley, Jodi M.; Sanches, Marcos; Benny, Claire
Highlights: Release from minimum legal drinking age (MLDA) laws is associated with sharp increases in crimes by young adults. Male crime patterns increased immediately after the drinking age. Female violent and disorderly-conduct crimes increased sharply following the MLDA. Raising the MLDA would likely attenuate crime in newly alcohol-restricted age groups. Abstract: Background: International debate is ongoing about the effectiveness of minimum legal drinking age (MLDA) laws. In Canada, the MLDA is 18 years of age in Alberta, Manitoba and Québec, and 19 in the rest of the country. Surprisingly few prior studies have examined the potential impacts of MLDA legislation on crime, and the current study addresses this gap. Methods: Regression-discontinuity analyses of police-reported criminal incidents from the 2009–2013 Uniform Crime Reporting (UCR) Survey, Canada's crime database. Results: Nationally, in comparison to males slightly younger than the MLDA, those just older than the MLDA had sharp increases in: all crimes, (7.6%; 95% CI = 3.7%–11%, P < 0.001); violent crimes, (7.4%; 95% CI = 0.2%–14.6%, P = 0.043); property crimes, (4.8%; 95% CI = 0.02%–9.5%, P = 0.049); and disorderly conduct, (29.4%; 95% CI = 15.6%–43.3%, P < 0.001). Among females, national criminal incidents increased sharply following the MLDA in: all crimes, (10.4%; 95% CI = 3.8%–17.0%, P = 0.002), violent crimes, (14.9%; 95% CI = 6.4–23.2, P = 0.001); and disorderly conduct, (35.3%; 95% CI = 11.6–58.9, P = 0.004). Among both males and females, there was no evidence of significant changes in cannabis- or narcotics-related crimes (quasi-control outcomes) vis-à-vis the MLDA ( P > 0.05). Conclusion: Release from drinking-age laws appears to be associated with immediate increases in population-level violent and nonviolent crimes among young people in Canada.